Percepção de ameaça de violência doméstica após uma promoção no trabalho da mulher - Napolis, Nathalia Soeiro Calabresi de (2023)
This dissertation aimed to analyse how a promotion in a woman's work can influence her marital relationship and what the consequences of this will be. As well as evaluating the moderating role of ambivalent sexism and the participant's gender in the perception of more negative consequences for women. For this purpose, a study was carried out with 303 university students (53.8% women), aged between 18 and 60 years (M = 23.73, SD = 6.25). The ethical procedures prescribed in resolution nº 466/2012 of the National Health Council (CNS) were followed and the terms of free and informed consent were duly signed by the participants. The compound was composed of three parts. The first part consisted of the Glick and Fiske Ambivalent Sexism Inventory. The second part consisted of an experimental manipulation scenario with two conditions. Then, the participants answered four questions, using a seven-point Likert scale, about the situation. Finally, participants answer sociodemographic questions. Data were analyzed with the help of JASP and Iramuteq software. The results reveal that there is a greater perception of the risk of domestic violence when the woman continues to take care of the house and children alone, because this dynamic is very present in abusive relationships. They also reveal that men perceive a significantly lower risk of domestic violence than women in both conditions. The textual analyzes adopted heterogeneous classes that raised questions such as: social gender roles, financial freedom, female double shifts, fragile masculinity, etc. Taken together, these results indicate that sexism still dictates marital relations and gender roles, and that its negative effect is associated with both its hostile and benevolent forms.